2017
DOI: 10.5530/jppcm.2017.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Delay in Tuberculosis Diagnosis on Pre-Diagnosis Cost

Abstract: Background: Delay in TB diagnosis can increase the financial burden of patients, especially those

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…This finding was quite similar to a study conducted in Yemen which reported high patients' costs among the TB patients with delay in diagnosis (delayed group). 32 One study in Tamil Nadu found that the patients who first visited a private facility were 17 times more likely to have high direct pre-diagnosis cost (more than the median $7.7) and 1.8 times more likely to have health system delay (more than the median 21 days) than the patients who first visited a public health facility. 7 Even after providing free diagnosis and treatment services in the public health facilities by the NTEP in India, 2 most of the patients seek care at a private health facility, which is associated with a longer health system delay and total delay.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was quite similar to a study conducted in Yemen which reported high patients' costs among the TB patients with delay in diagnosis (delayed group). 32 One study in Tamil Nadu found that the patients who first visited a private facility were 17 times more likely to have high direct pre-diagnosis cost (more than the median $7.7) and 1.8 times more likely to have health system delay (more than the median 21 days) than the patients who first visited a public health facility. 7 Even after providing free diagnosis and treatment services in the public health facilities by the NTEP in India, 2 most of the patients seek care at a private health facility, which is associated with a longer health system delay and total delay.…”
Section: Discussionmentioning
confidence: 99%